Heat Transfer Reduction due to a Ceiling-Mounted Barrier in an Enclosure with Natural Convection - Ilis, Gamze Gediz; Mobedi, Moghtada; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2011)
Effects of a ceiling-mounted barrier on natural convection heat transfer in a square cavity with differentially heated wall are numerically investigated. A limit case, in which the partition has small thickness and low thermal conductivity, is studied. The study is performed for nine different locations of barrier on the ceiling, two different lengths of barrier as 15 and 50% of the side wall, and Rayleigh numbers from 103 to 106. The vorticity and streamfunction approach is used to obtain velocity distribution, and the energy equation is solved to determine temperature field in the cavity. The variations of the local Nusselt number on the hot and cold walls and the change of mean Nusselt number with the location of barrier in the cavities with different Rayleigh numbers are presented. The obtained results show that a wall-mounted barrier can be used to reduce heat transfer rate through the cavity; however, its effectiveness depends on length and location of barrier and Rayleigh number.
Keywords: Square Cavity; Hot-Wall; Thin Fin; Triangular Enclosures; Trapezoidal Cavities; Bejans Heatlines; Visualization; Flow; Partitions; Generation